Teaching about dying and death: The 1918 Flu epidemic in South Africa (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
It seems obvious that while others around us are concerned with trying to understand the nature of the COVID-19 pandemic and the ways in which it has disrupted so much of our lives and professional work, history educators should be concerned rather to look back, to study previous epidemics for the light that they can shed on today. The 1918 ‘Spanish’ flu is a logical starting place. But it presents two obstacles: first, that there is so little that is truly comparable to the 2020 experience and, secondly, that the material of 1918 in South Africa is potentially so difficult to use in the classroom. How does one, for instance, teach about the number of cases where people narrowly avoided being buried alive, escaping in the nick of time. (And what about those who were not as fortunate?) This is an exploration of uncharted territory that presents an initial map to anyone who might be tempted to follow suit and put it to the test. As there is no ready model at hand to use to teach about dying and death in the history classroom, a sequence of five themes is proposed as a way in which one can approach the issue of mortality without coming at it head-on. The themes are explained and justified and an exemplar of a possible class activity is provided for each. The question posed is whether one should teach about dying and death in this way. The conclusion suggests what the possible benefits accruing might be.
Keywords: 1918 flu epidemic; Influenza; Spanish flu; COVID-19; Dying; Death; History curriculum; Human dignity; Empathy; Remembrance